Possible resolution of the B-meson decay polarization anomaly in R-parity violating supersymmetry; Physical Review D; Vol. 75, iss. 7 - Faessler A.; Gutsche Th.; Helo J. C.; Kovalenko S.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2007, 2007)
Title screen